Reveal the Diversity of Ichtyofauna Tambatan’s River North Labuhanbatu Regency - Dewi, Livia; Dimenta, Rivo Hasper (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The study aimed to determine the diversity of ichtyofauna species has been done in the Tambatan’s River, North Labuhanbatu Regency. This research applied by purposive sampling method to decided sampling collection which based on the environmental conditions of Tambatan’s River. Fish samples were collected using cast nets and gillnets. The collected data were analyzed using the Shannon-Wiener diversity index, evenness index, dominance index, similarity index, and Pearson’s correlation analysis. The results found 20 fish species from 5 families on Tambatan’s River. The largest family of fish species found from Cyprinidae’s (12 species), Bagridae’s (5 species), and the lowest found from Siluroidae’s, Mastacembelidae’s, Gobidae’s family an each 1 species. The result of the diversity index indicated that the 3 stations were classified in the medium category with range of 0.53-1.87. The result of pearson’s correlation describe fish biodiversity has strong positive correlation value to current velocity (0.927) and water transparency (0.927).